The role of local taxes on regional development in Jambi Province - Siti Hodijah (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2017)
Regional tax is a compulsory duty made by an individual or entity to a region without equal direct repayment that can be enforced under applicable legislation, which is used to finance the administration of local government and regional development. The role of local taxes is to assist the development of APBD (Local Government Budget) activities. Local governments are also exploring new local taxes annually that can be used for regional expenditure. This research was conducted in Jambi Province. This research uses descriptive method that the data obtained then arranged in such a way and analyzed correctly based on theory relevant to the problem. From the research results obtained growth of Jambi provincial tax in 2011-2015 fluctuate and tend to increase. Local tax contribution on Jambi provincial expenditure has decreased from year to year. Keywords: Local Tax, Regional Expenditure, Regional Development